2020
DOI: 10.1016/j.physd.2020.132399
|View full text |Cite
|
Sign up to set email alerts
|

Explosive, continuous and frustrated synchronization transition in spiking Hodgkin–Huxley neural networks: The role of topology and synaptic interaction

Abstract: Synchronization is an important collective phenomenon in interacting oscillatory agents. Many functional features of the brain are related to synchronization of neurons. The type of synchronization transition that may occur (explosive vs. continuous) has been the focus of intense attention in recent years, mostly in the context of phase oscillator models for which collective behavior is independent of the mean-value of natural frequency. However, synchronization properties of biologically-motivated neural mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…First, we establish the occurrence of a synchronization transition in this cognitive system. The amount of synchronization in neural networks with static synapses can be controlled upon changing the average synaptic strength [44,54]. In the present study synaptic strength is an autonomous variable which is modified by the internal dynamics of the network through the RL process.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, we establish the occurrence of a synchronization transition in this cognitive system. The amount of synchronization in neural networks with static synapses can be controlled upon changing the average synaptic strength [44,54]. In the present study synaptic strength is an autonomous variable which is modified by the internal dynamics of the network through the RL process.…”
Section: Resultsmentioning
confidence: 92%
“…t m i is the time that neuron i emits its m th spike. Next we evaluate a time-dependent order parameter [39,44,54]:…”
Section: Model and Methodsmentioning
confidence: 99%
“…Khoshkhou and Montakhab 13 investigated the influence of synaptic interaction (chemical and electrical) as well as structural connectivity on beta-band synchronization transition in network models of lzhikevich neurons, and these results indicated that biologically meaningful models of neural dynamics show a synchronization transition that relies on the average firing frequency of neurons, which is contrary to the case of simple phase oscillators. The authors also provided a systematic study of gamma-band synchronization in spiking Hodgkin-Huxley neurons which interact via electrical or chemical synapses, and concluded that gamma-rhythms are distinctly different from beta-rhythms in 14 . Boaretto et al 16 explored the non-monotonic synchronization transition in a Huber-Braun model, and showed that this non-monotonic phase transition occurs due to an interplay between the individual-regular behavior of the neurons and the influence of the synaptic current.…”
Section: Introductionmentioning
confidence: 99%
“…Neurons with intrinsic properties can be described by a large number of mathematical models. One kind of the well-known and biologically plausible models are the Hodgkin–Huxley equations and their simplified versions, which are widely used to analyze the synchronous in the neuronal network [ 10 12 ]. When a large number of conducted neuron models are considered, the number of coupled differential equations can be often a problem for computer simulations.…”
Section: Introductionmentioning
confidence: 99%